PROFESIONALISME KERJA PERANGKAT DESA DALAM PENYELENGGARAAN PELAYANAN ADMINISTRASI DI DESA KUBANG JAYA KECAMATAN SIAK HULU KABUPATEN KAMPAR TAHUN 2023 - Redho, Al; ', Wazni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The administration of village government requires the professionalism of village officials in providing administrative services to the community. However, in practice, there are often village officials who lack professionalism in performing their assigned duties and functions. In Kubang Jaya Village, which borders Pekanbaru City, there should be advantages in accessing various needs, receiving information more quickly, and having adequate facilities and infrastructure, especially in providing administrative services to the community. Nevertheless, in reality, the village still faces issues, such as officials who are unable to perform their duties and functions properly and who do not adhere to the regulations stipulated in the Kubang Jaya Village Regulation. The purpose of this study is to describe the professionalism of village officials in administering administrative services in Kubang Jaya Village, Siak Hulu District, Kampar Regency. The approach used in this study is qualitative, specifically descriptive qualitative research. Professionalism, in this context, refers to the attitude or state of performing tasks with high quality, timeliness, accuracy, and adherence to procedures that are easy to understand. According to Sedarmayanti, there are four indicators of professionalism: 1) competence, 2) effectiveness, 3) efficiency, and 4) responsibility. Keywords: Professionalism, Village Officials, Administrative Services